Do Environmental Regulations Effect FDI Decisions? The Pollution Haven Hypothesis Revisited - Haeyeon Yoon; Almas Heshmati (Institute of Labor Economics (IZA), 2017)
In an attempt to verify the pollution haven hypothesis, this study investigates the impact of environmental regulations on foreign direct investment (FDI). We use Korean outward FDI data covering the manufacturing sector for 2009-15. The study not only considers the stringency but also the enforcement of environmental regulations when measuring the degree of the host country's environmental regulations. Since the pollution haven's effects indicate moving the polluting production stages from the home country to other (host) countries, we distinguish between investments in the 'production' part from that in the non-production part using location information about the host country. The main results of the estimation of a FDI model show that the stricter the regulations in host countries in Asia the lower the FDI both intensively and extensively to those countries. This supports the prevalence of the effects of pollution havens. However, before we separate the FDI into the production part, the effect of environmental regulations on FDI is hindered by the FDI in the non-production part. The results indicate that environmental regulations are determinants of FDI in the production part, while environmental regulations do not have a significant effect on FDI decisions when the entire FDI is considered.
Keywords: F23; K32; L51; Q56; 330; pollution haven hypothesis; environmental regulation; foreign direct investment